Mit veränderten Reprisen II - Beghin, Tom (Ghent, Belgium Orpheus Institute, 2023)
Tom Beghin (clavichord and fortepiano); Afterwork Concert no. III (December 6, 2023)
Performing on clavichord and fortepiano, Tom Beghin explores a once lively practice of varying repeats through two sets of keyboard sonatas—for a total of twelve, to be digested in groups of three: CPE Bach’s Sechs Sonaten mit veränderten Reprisen, Wq 50 (1760) and Mozart’s six “Munich” Sonatas K 279–285 (1774–75). Sonatas by C. P. E. Bach (Wq. 50, 3) and W. A. Mozart (K. 280 and 281).
FRIS
Editorial review
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850